Safety and Efficacy of Degradable Starch Microspheres Transcatheter Arterial Chemoembolization (DSM-TACE) in the Downstaging of Intermediate-Stage Hepatocellular Carcinoma (HCC) in Patients With a Child-Pugh Score of 8-9 - Minici, Roberto; Ammendola, Michele; Manti, Francesco; Siciliano, Maria Anna; Minici, Marco; Komaei, Iman; Currò, Giuseppe; Laganà, Domenico (Frontiers in Pharmacology, 2021)
According to the EASL Guideline for the management of hepatocellular carcinoma, TACE is the first-line treatment recommended for intermediate-stage HCC. Furthermore, it’s widely accepted that patients beyond the Milan criteria can be considered for a liver transplant after successful downstaging to within Milan criteria. Response to downstaging treatments signiﬁcantly inﬂuences not just drop-outs, but also the rate of post-transplantation tumour recurrences. TACE with degradable starch microspheres represents an alternative to conventional TACE with Lipiodol and TACE with drug-eluting beads, and it leads to transient arterial occlusion allowing lower activation of hypoxia-inducible factors and less release of vascular endothelial growth factor, a promoter of neoangiogenesis, tumour proliferation and metastatic growth. In patients with intermediate-stage HCC and Child-Pugh score of 8 or 9, life expectancy may be dominated by the cirrhotic liver dysfunction, rather than by the tumour progression itself; hence, locoregional treatments might be also detrimental, precipitating liver dysfunction to an extent that survival is shortened rather than prolonged. Data on tolerability, toxicity and effectiveness of DSM-TACE are limited but encouraging. Between January 2015 and October 2020, 50 consecutive patients with intermediate-stage hepatocellular carcinoma and Child-Pugh score 8/9, who had undergone DSM-TACE as the first-line treatment, were eligible for the study. A total of 142 DSM-TACE was performed, with a mean number of 2.84 procedures per patient. The mean time-to-downstaging was 19.2 months, with 6 patients successfully downstaged. OS was about 100% at 6 months, 81.8% at 12 months and 50% at 24 months. 22 patients experienced adverse events after the chemoembolizations. Median OS and Safety of DSM-TACE in this study are comparable with other published investigations in this field. Furthermore, 12% of patients were successfully downstaged. Hence, the results of the current investigation demonstrate that DSM-TACE is effective and safe in intermediate-stage HCC, achieving an interesting downstaging rate. Such data were observed in the population subset with Child-Pugh score of 8 or 9, in which life expectancy may be dominated by the cirrhotic liver dysfunction, rather than by the tumour progression itself so that the achievement of a balance between safety and efficacy profile of the TACE treatment is crucial.